Perancangan Sistem Informasi Perpustakaan Berbasis Web Menggunakkan Metode Waterfall - Wilhelmus harjono; Kristianus Jago Tute (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2022)
SDK Buntal is an educational unit located in Golo Lijun Village, Elar District, East Manggarai Regency, NTT. In its activities, SDK Buntal has not implemented information technology in the school library. The library at the Buntal SDK currently still uses manual methods in processing libraries such as user data, searching and checking books to be ineffective because it takes a long time, book collection, borrowing and returning books, as well as late and lost data have not been properly structured. The purpose of this research is to design a Website-Based Library Information System in order to assist in collecting data and providing information for officers and members. In this Library Information System Research, the writer uses descriptive research, software design method using waterfall, and programming language using PHP and for database using MYSQL. The results achieved from this research, namely, can simplify and speed up the service process at the library and librarian can obtain work efficiency in managing library books, as well as presenting information more easily and interactively.